FUZZY TSUKAMOTO FOR DETECTION OF STUDENTS 'MENTAL HEALTH LEVEL - Nawindah Nawindah; Saskia Lydiani (Universitas Widyatama, 2021)
During a mental health pandemic, students who generally have higher mental health problems need a means of detection in order to find out the symptoms that arise. Fuzzy Tsukamoto was used to determine the level of mental health disorders in students with a sample of Budi Luhur University students. The results showed that by using the Tsukamoto fuzzy rule using the IF THEN, it was easy to determine the level of mental health disorders of students at a certain level.